TINJAUAN YURIDIS PERNIKAHAN BEDA AGAMA (STUDI KASUS PERKARA NO.650/PDT.P/2022/PN.JKT SEL.) - Renaning Galih Alif Nugrahani; Widhi Cahyo Nugroho (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Interfaith marriages has given rise to many interpretations regarding the validity of interfaith marriages in Indonesia, especially in Jakarta Selatan. In Indonesia, interfaith marriages are not regulated in a marriage law that applies in Indonesia. Trhe is a legal difference between the decision of the Supreme Court of the Republic Indonesia which grants permission to carry out interfaith marriages and the Ruling of the Constitutional Court of the Republic of Indonesia which rejects interfaith marriages. This study uses a normative juridical aspproach, in this research uses descriptive analytical research specifications, The data collection in this study used a literature study where the results of the research indicated that the Jurisprudence of the Jakarta Selatan District Court Case Study No.650/Pdt.P/2022/PN.Jkt Sel. used the Jurisprudence of the Supreme Court of the Republic of Indonesia No.1400k/Pdt/1986,etc. Also theis have own point of view in addressing legal conflicts the registration of interfaith marriages. In this case the judge also has a different perspective in deiding a case can handling, especially in the case ofminterfaith marriages.